Post-Marital Relationships Between Widow and Her Ex- Affines Among The Sundanese in Rural West Java - Mahira, Khansa; Mulyanto, Dede; Iskandar, Budiawati Supangkat (Universitas Negeri Semarang, 2025)
This article explores different types of relationships between widows and their ex-affines and explains the different factors of these relationships among the Sundanese people in rural West Java. The study was conducted by six widows with different experiences of their relationships with their ex-affinal kin using qualitative research methods with a case study approach. For this purpose, in-depth interviews and observational studies were conducted. Based on the results, we conclude that in the context of involuntary endogamous marriages, the relationship between widows and their ex-affinal kin takes the form of (1) friendship, (2) fictive daughter, (3) just another neighbor, (4) hostile neighbor, and (5) total stranger. These results are supported by factors such as (1) past personal relationships between the two people, (2) dependency on old age and social values in elderly care, and (3) the place of origin and residence of ex-husband. The nature of the relationships with ex-affine is not consistent across all categories. Ultimately, the classification of these relationships depends on the widow's specific situation after divorce or the death of her husband.